THE EFFECT OF THE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) LEARNING MODEL ON STUDENTS’ LEARNING MOTIVATION AND READING LITERACY - Sarwan Hamid; I Wayan Suastra; Ni Ketut Suarni (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to examine the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model on students' learning motivation and reading literacy. This study uses a quasi-experimental design with a non-equivalent posttest-only control group design. The study population was fifth-grade students at Muhammadiyah Elementary School in Kupang City, with a sample size of 58 students divided into an experimental group and a control group. Data collection was conducted using a learning motivation questionnaire and a reading literacy test that had undergone validity and reliability tests. Data analysis was performed using descriptive statistics and multivariate analysis (MANOVA). The results showed that the CIRC learning model had a significant simultaneous effect on students' learning motivation and reading literacy. Students taught using the CIRC model had higher learning motivation and reading literacy skills than students taught using conventional learning models. These findings indicate that the CIRC learning model is effective in improving the learning motivation and reading literacy of elementary school students.